2012
DOI: 10.4306/pi.2012.9.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Depression in East Asia: A Review of the Literature

Abstract: This current study's goal is to summarize the literature regarding Antenatal Depression (AD) in the East Asian countries of Taiwan, China (including Hong Kong and Macau), Japan, and Korea. The main search utilized a Pub med Chinese Electronic Periodical Service (CEPS) literature review using keywords 'AD', and 'Prenatal Depression' with searches for 'Japan', 'Korea', 'Taiwan', 'Hong Kong' and Macau'. The rates of AD in East Asia appear to be relatively close to those in the Western literature, although certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
2
15
2
Order By: Relevance
“…The result contradicts some previous studies, which found that the risk factors of antenatal depressive symptoms included lower income, lower education, smoking, alcohol abuse, and single status. Some studies in East Asia found that younger age and unemployment could also contribute to antenatal depression [7, 10, 20–22, 58]. This may be because our sample included a large proportion of pregnant women who were of young ages between 18–29 years old (82.4%).…”
Section: Resultsmentioning
confidence: 99%
“…The result contradicts some previous studies, which found that the risk factors of antenatal depressive symptoms included lower income, lower education, smoking, alcohol abuse, and single status. Some studies in East Asia found that younger age and unemployment could also contribute to antenatal depression [7, 10, 20–22, 58]. This may be because our sample included a large proportion of pregnant women who were of young ages between 18–29 years old (82.4%).…”
Section: Resultsmentioning
confidence: 99%
“…No significance was observed for women aged 35 years or more. Previous studies have shown that younger antenatal and postnatal women have higher risks of experiencing depressive symptoms [ 61 63 ]; older women are believed to have the ability to adapt to changes in the external environment and to have fewer mood disorders [ 64 ]. The nonsignificant association between secondhand smoke exposure and depression for women aged <25 years in our study is probably due to the small sample size and its limited statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…Schatz [21], in their review of antenatal depression in East Asia (e.g. Taiwan, China, Japan, and Korea), found that Chinese individuals have common risk factors associated with antenatal depression in both Western and Eastern populations, including: age [17,22], education level [23], occupation, number of miscarriages/abortions [24].…”
Section: Introductionmentioning
confidence: 99%